(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The main objective of the research is to study and analyze the use of digital transformation to support continuous improvement and achieve sustainable quality, thereby improving quality, raising performance, reducing costs, and enhancing sustainable competitive advantage. To achieve this objective, the researcher conducted a survey consisting of (240) items distributed to information systems specialists, cost accountants, managers, and faculty members. The research concluded that there is a significant effect between digital transformation and continuous improvement methodologies and achieving sustainable quality. Digital transformation is one of the critical factors in achieving sustainable quality within organizations, as it helps improve operations, raise performance efficiency, and enhance customer satisfaction through smart technologies. Additionally, it supports environmental sustainability by reducing resource consumption and improving supply chains, which helps companies achieve high-quality performance. The research recommends investing in modern technologies such as artificial intelligence, the Internet of Things, and cloud computing to support continuous improvement processes and thus achieve sustainable quality.